1998
DOI: 10.1111/1467-8535.00055
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between cognitive style and academic achievement

Abstract: Field independent students are generally expected to perform better academically than those who are field dependent, and this is particularly marked in distance learning where students learn without the traditional support offered in conventional instruction. In this paper two studies of the relationship between field dependence and academic learning in the context of distance learning are reported with Bachelor of Health nursing students in Hong Kong. In both studies field independent nurses performed signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 24 publications
2
20
0
Order By: Relevance
“…Cognitive styles have been explored in fields such as health sciences (Luk, 1998), psychology (Baron-Cohen & Hammer, 1997) and applied linguistics (Abraham, 1981(Abraham, , 1983). Carroll and Sapon (1958) were the first applied linguists who showed field independence is significantly related to foreign language aptitude, as measured by the Modern Language Aptitude Test.…”
Section: Introductionmentioning
confidence: 99%
“…Cognitive styles have been explored in fields such as health sciences (Luk, 1998), psychology (Baron-Cohen & Hammer, 1997) and applied linguistics (Abraham, 1981(Abraham, , 1983). Carroll and Sapon (1958) were the first applied linguists who showed field independence is significantly related to foreign language aptitude, as measured by the Modern Language Aptitude Test.…”
Section: Introductionmentioning
confidence: 99%
“…Questions (3,6,15,16,20,) which directly address the Field Independent participants' attitudes toward reading comprehension and their preferences received high numerical value for mean score (mean=1.7 and p=50%). Similarly, questions (6,8,16) received the highest mean score (mean=3.30 and p=60%). Question 3 asks about finding the supporting paragraphs, the analysis shows that more than 70% of the Field Independent participants could understand the relations and main idea supporting paragraphs.…”
Section: Theory and Practice In Language Studies 2145mentioning
confidence: 94%
“…The results of this survey confirmed that Iranian Field Independent EFL learners' at intermediate proficiency level, are better in understanding the specific information, covert message in the text, inferencing, and treat reading text as a part. Davis ,1991;Goodenough,1976;Davey and Menke, 1989;Luk, 1998;Ahmady&Yamini, 1992 ).There exists a relationship between FIELD Dependency / Independency and reading comprehension. The obtained results might be attributed to some factors.…”
Section: Theory and Practice In Language Studies 2145mentioning
confidence: 99%
“…The total possible score on the GEFT is, therefore, 18 with a mean of 11. The test takers achieving a GEFT score below and above the mean are labeled FD and FI, respectively (e.g., Luk, 1998). Gholami (2006) developed four versions of a close multiple choice item test (CMCIT) on 60 adjectives, 60 adverbs, 60 nouns and 60 verbs comprising the authentic and unmodified text "why don"t we just kiss and make up" (Dugatkin, 2005).…”
Section: Group Embedded Figure Testmentioning
confidence: 99%